50 Using GPS and Genomic Technology to Provide a More Accurate Estimate of Bull Power in Western Intermountain Beef Systems. (8th October 2021) - Garcia, Matthew D; Chapman, Kim; Heaton, Kevin; Dallin, Josh; Rood, Kerry; Thacker, Eric; Hadfield, Jacob; Larsen, Ryan
Abstract: The objective of this study was to utilize GPS technology and genomic parentage testing to provide a more accurate measurement of bull power in the intermountain west beef production system. Breeding seasons are typically conducted on large, remote pastures, leading to current estimates of bull:cow ratios (1:20 or 1:25) possibly being inaccurate. With advances in genetic testing, parentage of calves can be obtained allowing producers to review which calves were sired from specific bulls, or how many cows each bull serviced (bull power). Our study fit 5 bulls from the same herd with GPS collars and collected hair samples for future DNA extraction prior to the 2018 breeding season. Bull movement was tracked over a 90-day breeding season on a large grazing allotment on the southern Utah and northern Arizona border. The GPS collars collected measurements of total distance traveled per day and distance traveled away from water, along with geocoordinates. Upon completion of the breeding season, collars were removed and data retrieved. At calving, biological material was collected and parentage testing of 104 calves was conducted and parentage determined. Results of parentage testing revealed that actually 6 bulls sired calves during the 2018 breeding season. The ranch's bulls sired 72 (69%) calves (30, 16, 14, 10 and 2 calves, respectively). Thirty-two (31%) calves were sired by bulls from herds that grazed nearby. Interesting to note is the producer was unaware of any non-herd bulls co-mingling with this herd. While results from the current study are very preliminary, they do validate the importance of verifying bull power and sire identification to critically evaluate sire performance and increase the accuracy of selection in breeding replacements. The information presented herein may prove useful as a future selection tool to identify bulls that are high performing during breeding season in the intermountain west.